If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(v + -9) + -7 = -4(-5v + 6) + -9v Reorder the terms: 3(-9 + v) + -7 = -4(-5v + 6) + -9v (-9 * 3 + v * 3) + -7 = -4(-5v + 6) + -9v (-27 + 3v) + -7 = -4(-5v + 6) + -9v Reorder the terms: -27 + -7 + 3v = -4(-5v + 6) + -9v Combine like terms: -27 + -7 = -34 -34 + 3v = -4(-5v + 6) + -9v Reorder the terms: -34 + 3v = -4(6 + -5v) + -9v -34 + 3v = (6 * -4 + -5v * -4) + -9v -34 + 3v = (-24 + 20v) + -9v Combine like terms: 20v + -9v = 11v -34 + 3v = -24 + 11v Solving -34 + 3v = -24 + 11v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-11v' to each side of the equation. -34 + 3v + -11v = -24 + 11v + -11v Combine like terms: 3v + -11v = -8v -34 + -8v = -24 + 11v + -11v Combine like terms: 11v + -11v = 0 -34 + -8v = -24 + 0 -34 + -8v = -24 Add '34' to each side of the equation. -34 + 34 + -8v = -24 + 34 Combine like terms: -34 + 34 = 0 0 + -8v = -24 + 34 -8v = -24 + 34 Combine like terms: -24 + 34 = 10 -8v = 10 Divide each side by '-8'. v = -1.25 Simplifying v = -1.25
| 15f+6n=8f | | 1/2(4a-8) | | 16x^2-120x+25=0 | | 3q^2+17q+14=0 | | 16=5x-7 | | 2cos^2x-9cosx-5=0 | | 5n*n+40n=5n | | 15+x=18x | | 2t^2-13t+15=0 | | n/9=72 | | 6-9x+8=10+4x | | 15+x=-4+x | | 8x+5=y | | 3cos(2X)-2sin(2x)=(a)sin(bx+c) | | (2x+5)5= | | 2f-35=f+9 | | 2f-35=f+8/9 | | v=1/3*3.14*(7*x^4)^2*6 | | 3x^2-147+12=0 | | 3j^2+13j+10=0 | | 1/2*-5 | | -8x^2+18x-9=0 | | 3x^2-49+12=0 | | 8g*g*g-2g*g=2g*g-5g*g | | 2a-2=82 | | (-8+5x)-(-2x-9)= | | 0.2x^2-9x+0.2=0 | | 3a-54=a | | 0.2x^2-9x+0.2=o | | a+5+8=15 | | (9x^2-10x)/11x^2 | | 7(x+6)=7(x+10) |